A workplace-based risk assessment improves predicted lifetime cardiovascular disease risk in male steelworkers. (September 2016) - Gray, B.J.; Bracken, R.M.; Turner, D.; Long, S.J.; Thomas, M.; Williams, S.P.; Davies, C.A.; Morgan, K.; Williams, M.; Rice, S.; Stephens, J.W.
Highlights: This article presents 'real life' data. Shift workers and day workers equally as likely to attend follow-up appointments. Prevalence of obesity remains a public health issue in the workplace. Lifetime CVD risk can be improved by workplace-based health initiatives. Greater improvements observed in more deprived employees.